Efficiency of autologous stem cell collection: Comparison of three different cell separators. Issue 1 (February 2017) - Deneys, Véronique; Fabry, Annick; Van Hooydonk, Maryse; Sonet, Anne; André, Marc; Bourgeois, Marc; Botson, Françoise
Abstract: Peripheral blood progenitor cells (PBPC) infusion allows rapid haematological recovery after high dose chemotherapy. Efficient PBPC collection is therefore essential as rescue therapy for transplantation. In order to validate a new equipment (ComTec ®, Fresenius Kabi), we compared the efficiency of three cell separators for PBPC collection in patients with haematological malignant diseases. From June 2014 to December 2015, 83 PBPC were collected in 48 patients. Three aphaeresis machines were used: Cobe Spectra ® (Terumo BCT, 11), Amicus ® (Fenwall, 30), and ComTec ® (Fresenius Kabi, 42). The median collection efficiency was similar between the three separators. The evaluation of cell contamination in the final product revealed a lower red cell contamination with Spectra ® and ComTec ®, whereas the platelet contamination was lower with Amicus ® . The new equipment has been validated and can be further used in routine, with a total running cost that turned out to be quite lower. Each separator has its own characteristics and advantages. Further study is needed to suggest that the choice of separator could be guided following the patient's blood characteristics.